2019
DOI: 10.3390/rs11050543
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Harvested Sites in a Forested Boreal Mountain Catchment through Global Forest Watch

Abstract: Global Forest Watch (GFW) provides a global map of annual forest cover loss (FCL) produced from Landsat imagery, offering a potentially powerful tool for monitoring changes in forest cover. In managed forests, FCL primarily provides information on commercial harvesting. A semi-autonomous method for providing data on the location and attributes of harvested sites at a landscape level was developed which could significantly improve the basis for catchment management, including risk mitigation. FCL in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The SR16 maps are regularly updated for growth using linking models with updated parameter estimates using current NFI data. Changes due to larger removals such as harvests are updated by setting the predicted forest attributes in pixels with a Global Forest Watch change (Hansen et al 2013 ; Rossi et al 2019 ) to zero. This also provides harvested volume as a new map product.…”
Section: Current Developments and The Foreseeable Futurementioning
confidence: 99%
“…The SR16 maps are regularly updated for growth using linking models with updated parameter estimates using current NFI data. Changes due to larger removals such as harvests are updated by setting the predicted forest attributes in pixels with a Global Forest Watch change (Hansen et al 2013 ; Rossi et al 2019 ) to zero. This also provides harvested volume as a new map product.…”
Section: Current Developments and The Foreseeable Futurementioning
confidence: 99%
“…Our rebuttal already explained that the change of algorithm in 2015 was totally undocumented: the websites by GFC [2] and GFW [3] include warnings on combining two time series, 2001-2010and 2011-2019(and this was clearly acknowledged in Ceccherini et al 2020), but do not include any warning against trend analyses after 2012.…”
Section: On the Correct Use Of The Global Forest Change Datasetmentioning
confidence: 99%
“…• Rossi et al (2019), assessing forest harvesting in Norway, concluded that "Overall, [GFC] proved to be a useful dataset for the purpose of assessing harvesting activity under the given conditions". A marked increase in harvest is shown in 2016 (their figure 12), but it is not discussed as a possible inconsistency in the dataset.…”
Section: On the Correct Use Of The Global Forest Change Datasetmentioning
confidence: 99%
“…Intense forest loss is a well studied process in Europe (Senf et al, 2018;Ceccherini et al, 2020;Senf and Seidl, 2021). Discrepancies between national forest inventories and remote sensing technique has led to disagreements in Sweden (Paulsson et al, 2020), Finland (Korhonen, 2020), and Norway (Rossi et al, 2019). For instance, it was found that existing remote sensing products are deemed not fit for these types of analysis (Palahí et al, 2021).…”
Section: Time-series Analysis Interpretations and Challengesmentioning
confidence: 99%